Seropositivity and geographical distribution of Strongyloides stercoralis in Australia: A study of pathology laboratory data from 2012-2016. - Jennifer Shield; Sabine Braat; Matthew Watts; Gemma Robertson; Miles Beaman; James McLeod; Robert W Baird; Julie Hart; Jennifer Robson; Rogan Lee; Stuart McKessar; Suellen Nicholson; et al. (Public Library of Science (PLoS), 2021)
Background There are no national prevalence studies of Strongyloides stercoralis infection in Australia, although it is known to be endemic in northern Australia and is reported in high risk groups such as immigrants and returned travellers. We aimed to determine the seropositivity (number positive per 100,000 of population and percent positive of those tested) and geographical distribution of S. stercoralis by using data from pathology laboratories. Methodology We contacted all seven Australian laboratories that undertake Strongyloides serological (ELISA antibody) testing to request de-identified data from 2012-2016 inclusive. Six responded. One provided positive data only. The number of people positive, number negative and number tested per 100,000 of population (Australian Bureau of Statistics data) were calculated including for each state/territory, each Australian Bureau of Statistics Statistical Area Level 3 (region), and each suburb/town/community/locality. The data was summarized and expressed as maps of Australia and Greater Capital Cities. Principal findings We obtained data for 81,777 people who underwent serological testing for Strongyloides infection, 631 of whom were from a laboratory that provided positive data only. Overall, 32 (95% CI: 31, 33) people per 100,000 of population were seropositive, ranging between 23/100,000 (95% CI: 19, 29) (Tasmania) and 489/100,000 population (95%CI: 462, 517) (Northern Territory). Positive cases were detected across all states and territories, with the highest (260-996/100,000 and 17-40% of those tested) in regions across northern Australia, north-east New South Wales and north-west South Australia. Some regions in Greater Capital Cities also had a high seropositivity (112-188/100,000 and 17-20% of those tested). Relatively more males than females tested positive. Relatively more adults than children tested positive. Children were under-represented in the data. Conclusions/significance The study confirms that substantial numbers of S. stercoralis infections occur in Australia and provides data to inform public health planning.